Some modern German fairy stories - Huse, Helen Knostman (My University, 1908)
Introduction: The following stories are translations from the “Neuerdeutscher Marchenschatz” (7 Sonderheft der “Woche”) – August Scherl G.m,b.h., Berlin. The book contains the thirty best stories from a collection of four thousand and twenty-five written in a story-writing competition.
Citation: Huse, Helen Knostman. Some modern German fairy stories. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Fairy Tales; German Literature; Translations; Graduating theses; Senior theses; Theses